The Smeds and the Smoos - Donaldson, Julia; Scheffler, Axel (New York : Scholastic Press, 2019)
"The Smeds (who are red) never mix with the Smoos (who are blue). So when a young Smed and Smoo fall in love, their families strongly disapprove. But peace is restored and love conquers all in this happiest of love stories. There is even a gorgeous purple baby to celebrate!"--OCLC.
2.2
K-3
K-3
Keywords: Extraterrestrial beings -- Juvenile fiction; Families -- Juvenile fiction; Prejudices -- Juvenile fiction; Toleration -- Juvenile fiction; Extraterrestrial beings -- Fiction; Family life -- Fiction; Prejudices -- Fiction; Toleration -- Fiction; Aliens (Fictional characters) -- Fiction; Family life -- Fiction; Prejudices -- Fiction; Toleration -- Fiction; Picture books; Stories in rhyme